2016
DOI: 10.1093/scan/nsw102
|View full text |Cite
|
Sign up to set email alerts
|

Awake canine fMRI predicts dogs’ preference for praisevsfood

Abstract: Dogs are hypersocial with humans, and their integration into human social ecology makes dogs a unique model for studying cross-species social bonding. However, the proximal neural mechanisms driving dog–human social interaction are unknown. We used functional magnetic resonance imaging in 15 awake dogs to probe the neural basis for their preferences for social interaction and food reward. In a first experiment, we used the ventral caudate as a measure of intrinsic reward value and compared activation to condit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 71 publications
2
46
0
Order By: Relevance
“…Web5 advised to "[give]…food one time, then play with a toy, then just rub his ears and praise him." In fact, in a non-learning context, a recent study using fMRI and preference tests suggested that some dogs prefer social praise over food rewards (Cook et al 2016). Another study found that dogs preferred petting over praise (Feuerbacher and Wynne 2015).…”
Section: How the Signal Should Be Usedmentioning
confidence: 99%
“…Web5 advised to "[give]…food one time, then play with a toy, then just rub his ears and praise him." In fact, in a non-learning context, a recent study using fMRI and preference tests suggested that some dogs prefer social praise over food rewards (Cook et al 2016). Another study found that dogs preferred petting over praise (Feuerbacher and Wynne 2015).…”
Section: How the Signal Should Be Usedmentioning
confidence: 99%
“…Censoring was performed with respect to both signal intensity and motion, in which voxels with greater than 3% signal change from the mean and volumes with more than 1 mm of scan-to-scan movement were flagged as spurious and censored from further analysis. Smoothing, normalization, and motion correction parameters were identical to those described in previous studies [25]. The Advanced Normalization Tools (ANTs) software [26] was used to spatially normalize the mean of the motion-corrected functional images to the individual dog’s structural image.…”
Section: Methodsmentioning
confidence: 99%
“…Regions that are said to support conditioned associations to odor 97 stimuli include the orbitofrontal and perirhinal cortices when learning odor categories. Even on 98 the first day of conditioning, activity within the hippocampus predicted the olfactory 99 associations that would be remembered one week later (Howard, Kahnt, & Gottfried, 2016 show differential activation in the reward processing regions of the brain such as the caudate nucleus to social or food rewards (Cook, Prichard, Spivak, & Berns, 2016). And dogs show higher 137 activation in the amygdala and caudate to odors associated with familiar humans and dogs than 138 to odors of strangers .…”
Section: Introductionmentioning
confidence: 99%